Redes interorganizacionais e inovação: o caso do pólo joalheiro de Belém - Castro, Renato Brito de (2008)
This work is a case study based on Belém Jewelry Pole, whose main issue is to understand how the social network (which the Pole is inserted) influences on innovation process on this area. The main objective is to analyze how interorganizational networks impacted/impact on the potential for innovation, creating both limits and opportunities for the companies development. The adopted method analyzed the historical jewelry industry trajectory since the beginning of mineral extraction in the city of Itaituba (in the Pará State) until nowadays. Primary and secondary data were used allowing the view of the dynamics of the network during transformation periods of the main involved actors in the process. The prospect of embeddedness structural as analysis technique allowed verifying the quality of interactors ties, as well as the visualization of their structures. During the jewelry industry trajectory was verified a change in the quality of social relations, modifying the information flow, trust and associations of various links in the production chain. Both direct and indirect ties facilitated the access to remote networks entering new information related to new products, processes and market aspects. This interaction has led to raising the innovation potential causing a qualitative and quantitative improvement in competitiveness of organizations. Some embedded ties allowed the formation of partnerships bringing various economic earnings for those involved in the relationship. Thus, it is understood how aspects related to the position, architecture and quality of ties in a wide social network influenced on the innovation process and eventual jewelry industry trajectory